Chemical Profile and Antibacterial Activity of a Novel Spanish Propolis with New Polyphenols also Found in Olive Oil and High Amounts of Flavonoids - María Coronada Fernández-Calderón; María Luisa Navarro-Pérez; María Teresa Blanco-Roca; Carolina Gómez-Navia; Ciro Pérez-Giraldo; Virgina Vadillo-Rodríguez (Molecules, 2020)
Propolis is a natural product obtained from hives. Its chemical composition varies depending on the flora of its surroundings, but nevertheless, common for all types of propolis, they all exhibit remarkable biological activities. The aim of this study was to investigate the chemical composition and antimicrobial activity of a novel Spanish Ethanolic Extract of Propolis (SEEP). It was found that this new SEEP contains high amounts of polyphenols (205 ± 34 mg GAE/g), with unusually more than half of this of the flavonoid class (127 ± 19 mg QE/g). Moreover, a detailed analysis of its chemical composition revealed the presence of olive oil compounds (Vanillic acid, 1-Acetoxypinoresinol, p-HPEA-EA and 3,4-DHPEA-EDA) never detected before in propolis samples. Additionally, relatively high amounts of ferulic acid and quercetin were distinguished, both known for their important therapeutic benefits. Regarding the antimicrobial properties of SEEP, the minimal inhibitory and bactericidal concentrations (MIC and MBC) against Staphylococcus epidermidis strains were found at the concentrations of 240 and 480 µg/mL, respectively. Importantly, subinhibitory concentrations were also found to significantly decrease bacterial growth. Therefore, the results presented here uncover a new type of propolis rich in flavonoids with promising potential uses in different areas of human health.